SOLUTION OF CANCEROGEN ASBESTOS PROBLEMS IN OBTAINING HARMLESS FIBRE PRODUCTS (Scientific journal of the Fergana State University, 2023)
The article presents the ways of obtaining ecologic harmless composite materials based on mineral fibers in the replacement of asbestos containing goods